Status of arsenic test and exposure to arsenic-contaminated tubewell water: a population-based study in Southern Bangladesh - Dey, Nepal C; Rana, AKM Masud; Barua, Milan K.; Kabir, Babar (BRAC Research and Evaluation Division (RED), 2019)
This study explores the status of arsenic test of tubewell and exposures to arsenic-contaminated tubewell water in the arsenic prone southern Bangladesh. Through a survey of 6,593 households, a total of 3,812 tubewells were sampled at baseline (2006/07) and 3,591 at midline (2009). Households were selected through multi-stage sampling procedure where each sub-district was considered as a cluster. Findings reveal that proportion of unmarked (to identify presence of arsenic) tubewells increased from 80% at baseline to 90% at midline (p<O.OOI). Proportion of tested tubewells was significantly decreased from 75% at baseline to 69% at midline (p<O.OOI). Of the tested tubewells, 60% was reported to be free from arsenic contamination. Around 44% of the household members usually drink water from arsenic contaminated tubewells. This study underlines that information, education and communication campaigns should be strengthened to raise awareness regarding negative effect of arsenic on health.